2016
DOI: 10.1109/jstars.2016.2555960
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study and Analysis Among ATGP, VCA, and SGA for Finding Endmembers in Hyperspectral Imagery

Abstract: Endmember finding has become increasingly important in hyperspectral data exploitation because endmembers can be used to specify unknown particular spectral classes. Pixel purity index (PPI) and N-finder algorithm (N-FINDR) are probably the two most widely used techniques for this purpose where many currently available endmember finding algorithms are indeed derived from these two algorithms and can be considered as their variants. Among them are three well-known algorithms derived from imposing different abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 29 publications
(59 reference statements)
0
25
0
Order By: Relevance
“…In this regard, automated endmember bundles (AEB) [19] has established endmembers sets by executing standard endmember extraction algorithms such as N-FINDR [20], orthogonal subspace projection (OSP) [21], unsupervised fully constrained least squares (UFCLS) [22], iterative error analysis (IEA) [23] and vertex component analysis (VCA) [24] and clustering the resulted endmembers from different methods. Recently, the authors in [25] showed that VCA is essentially the same as simplex growing algorithm (SGA) [26] as long as their initial conditions are the same. So, other conventional endmember extraction algorithms such as SGA can be used in AEB.…”
Section: Establishing a Set Of Spectral Variabilities For Each Endmembermentioning
confidence: 99%
“…In this regard, automated endmember bundles (AEB) [19] has established endmembers sets by executing standard endmember extraction algorithms such as N-FINDR [20], orthogonal subspace projection (OSP) [21], unsupervised fully constrained least squares (UFCLS) [22], iterative error analysis (IEA) [23] and vertex component analysis (VCA) [24] and clustering the resulted endmembers from different methods. Recently, the authors in [25] showed that VCA is essentially the same as simplex growing algorithm (SGA) [26] as long as their initial conditions are the same. So, other conventional endmember extraction algorithms such as SGA can be used in AEB.…”
Section: Establishing a Set Of Spectral Variabilities For Each Endmembermentioning
confidence: 99%
“…Here we use three different algorithms for extracting endmembers from hyperspectral data. The first one is Automatic Target Generation Process (ATGP) that finds its targets by using a sequence of orthogonal subspaces with the maximal orthogonal projections [2], [5], [7], [8] where ATGP considered the unsupervised version of Orthogonal Subspace Projection (OSP) algorithm. The second used algorithm is the Simplex Growing Algorithm (SGA) [3], [8] which finds its endmembers by growing a simplex, vertex by vertex, until it reaches the required endmembers represented by vertices of simplex.…”
Section: Introduction Imentioning
confidence: 99%
“…The first one is Automatic Target Generation Process (ATGP) that finds its targets by using a sequence of orthogonal subspaces with the maximal orthogonal projections [2], [5], [7], [8] where ATGP considered the unsupervised version of Orthogonal Subspace Projection (OSP) algorithm. The second used algorithm is the Simplex Growing Algorithm (SGA) [3], [8] which finds its endmembers by growing a simplex, vertex by vertex, until it reaches the required endmembers represented by vertices of simplex. The last used algorithm is the Vertex Component Analysis (VCA) [4], [8], it is an OP-based EEA that is characterized by computational complexity reduction by replacing simple volume calculation with OP and growing nonnegative convex hulls, vertex by vertex, until it builds a pvertex convex hull (p denotes the endmembers required to be extracted).…”
Section: Introduction Imentioning
confidence: 99%
See 2 more Smart Citations